European Society for Medical Oncology (ESMO) position paper on supportive and palliative care - Jordan, Karin; Aapro, M.; Kaasa, S.; Ripamonti, C. I.; Scotté, F.; Strasser, F.; Young, A.; Bruera, E.; Herrstedt, J.; Keefe, D.; Laird, B.; Walsh, D.; et al. (Annals of oncology, 2018)
Abstract. Oncology has come a long way in addressing patients’ quality of life, together with developing surgical, radio-oncological and medical anticancer the